Revaluation of the available energy of difructose anhydride III and maltobionic acid based on the fermentability of breath hydrogen excretion in healthy humans. Issue 1 (1st January 2021) - Tanabe, Kenichi; Okuda, Asuka; Nakamura, Sadako; Oku, Tsuneyuki
ABSTRACT: The relative available energy (RAE) based on the fermentability of breath hydrogen excreted by gut microbiota was assessed using a method accepted by the Japanese Society for Dietary Fiber Research. The purpose of this study was to evaluate RAE of difructose anhydride III (DFA III) and maltobionic acid (MA). In this study, which had a within-subject, repeated measures design, 11 healthy female participants ingested 5 g of DFA III, MA, and fructooligosaccharide, which has RAE of 2 kcal/g. Breath hydrogen was collected 12 times up to 14 h after meal consumption and measured using gas chromatography, and the area under the curves (AUCs) was calculated 0–14 h after ingestion. Compared with the AUCs of breath hydrogen excretion related to the ingested fructooligosaccharide for 14 h, those of DFA III and MA were 40.5% and 23.1%, respectively. RAE was 0.81 kcal/g for DFA III and 0.46 kcal/g for MA, respectively.